Clinicobiological Profile and Evolution of Patients with Acute Kidney Injury Requiring Emergency Hemodialysis in an Ivorian Referral Hospital - François , Kissou Pegdebamba; Cyr, Guei Monlet; Tchoupé Djoumbissie Marius; Semde Aoua; Moudachirou Mohamed Ibrahim Alex; Ouedraogo Saidou; Togo Abdoulaye; Diopoh Patrick Sery; Yao Kouame Hubert (HEALTH SCIENCES AND DISEASE, 2022)
ABSTRACT Introduction. Due to late referral of the pads to the nephrologist and the lack of medical follow-up, many patients are admitted with complications from kidney disease requiring the urgent start of hemodialysis. The aim of this work was to study the clinico-biological and evolutionary profile of patients with Acute Kidney Injury (AKI) who underwent emergency hemodialysis in a referral hospital of Ivory Coast. Methods. This was a retrospective, descriptive and analytical study which took place from January 1 to December 31, 2016, in the Nephrology Department at the University Teaching Hospital of Yopougon in Ivory Coast. All patients who received an emergency hemodialysis session during the study period were identified through the registry. Those who were at their first session for AKI, at least 16 years old and whose clinical records were available were selected. Results. We collected 36 medical records of patients with an average age of 41.31±13.93 years. Patients past medical history showed high blood pressure (HBP) (27.78%), herbal medicine consumption (80.56%) and HIV infection (19.44%). The main clinical signs were Elevated BP (38.89%), neurogical disorders (41.66%), edema (22.22%) with sometimes acute pulmonary edema (2,78%) and anuria (19.44%). Organic AKI accounted for more than 80% of cases. The main indications of hemodialysis were: uremic encephalopathy (41.67%), other severe uremic complications (25%), persistent anuria (19.44%) and threatening hyperkaliemia (11.11%). Death occurred in 30.55% with sepsis as the main cause (72.72%). Conclusion. AKI requiring hemodialysis is associated with high mortality and deaths were more often caused by sepsis. RÉSUMÉ Introduction. Le retard accusé pour leur prise en charge fait que nombreux sont les patients souffrant d’insuffisance rénale qui arrivent dans les hôpitaux avec des complications sévères nécessitant des séances d’hémodialyse en urgence. Le but de ce travail était d’étudier le profile clinico-biologique et évolutif des patients atteints de lésion rénale aiguë (LRA) et hémodialysés en urgence dans un hôpital de référence en Côte d’Ivoire. Méthode. Il s’est agi d’une étude rétrospective, descriptive et analytique qui s’est déroulée du 1er janvier au 31 décembre 2016 dans le service de néphrologie du CHU de Yopougon en Côte d’Ivoire. Tous les patients qui étaient à leur première séance d’hémodialyse pour une LRA et âgés de plus de 16 ans ont été inclus dans l’étude. Résultats. Nous avons colligé 36 patients avec un âge moyen de 41.31±13.93 ans. Les principaux antécédents des patients étaient une HTA (27,78 %), une consommation de médicaments traditionnels (80,56 %) et une infection au VIH (19,44 %). Les principaux signes cliniques étaient l’HTA (38,89 %), les troubles neurologiques (41,66 %), les œdèmes (22,22 %) avec l’OAP (2,78 %) et l’anurie (19,44 %). La LRA était organique dans plus de 80 % des cas. Les principales indications de l’hémodialyse étaient l’encéphalopathie urémique (41,67 %), les autres complications urémiques (25 %), l’anurie persistante (19,44 %), l’hyperkaliémie menaçante (11,11 %). La mortalité était de 30,55 % et le sepsis en était la principale cause. Conclusion. La LRA nécessitant une hémodialyse en urgence était associée à une forte mortalité et le sepsis le plus souvent incriminée.